Factors Which Contribute to Students' Persistence: A Study on "Sahabat Anak" Non-Formal School for Marginal Children - Natalia Ajiningtyasasih; Fentiny Nugroho (Asian Social Work Journal, 2020)
Generally, the school drop-out rate of marginal children is high. However, some of them have high persistence and can complete their education. This research aims to describe the factors that play a crucial role in forming student persistence and analyze efforts and challenges encountered by Pusat Kegiatan Anak (PKA/Children’s Activity Center) “Sahabat Anak” in maintaining and increasing their students' persistence. This study used a qualitative approach with descriptive research. Data collection techniques employed are in-depth interviews and documentary studies involving four school alumni who have continued their education to formal schools, two teachers, and two education staff of PKA “Sahabat Anak” Non-formal School. This study finds that social support from parents and closest people is a very significant factor in building the persistence of students of PKA “Sahabat Anak” Non-formal School. The School makes efforts to build children's persistence by conducting quarterly evaluations, parental training, and a home visit. However, influences from the social environment become a big challenge for these efforts. Social workers shall play a key role in addressing these issues.